The Effect of Biogel Using Biomagnetic Energy in the Treatment of Acute Pain in the Upper Extremity and Spine: A Randomized Controlled Trial - Kayır, Tuba; Demir , Emre; Alıç, Taner; Kayır, Selçuk (European Journal of Therapeutics, 2023)
Objective: Pain is a public health problem, which is caused by various etiological factors and leads to diminished quality of life and decreased workforce. The aim of this study was to determine whether Biogel has an effect in the treatment of pain. Methods: Patients due to acute pain in the upper extremity and/or trunk were divided into two groups as treatment and placebo by randomization method. For the patients in the treatment group,the non-interventional Biogel was applied for 10 minutes. For the control group, a non-interventional placebo was applied for 10 mins. A record was made of patient demographic data,the region of the pain, and mean arterial pressure (MAP) values before and after the application. All the patients in both groups were administered a Visual Analogue Scale (VAS) to evaluate pain severity,and the Nottingham Health Profile (NHP) before and after the applications. The data obtained were compared. Results: In the biogel group, a statistically significant decrease was determined in the NHP-P values after treatment compared to before treatment (P<0.001). In the placebo group,no statistically significant difference was determined in the NHP-P values before and after treatment (P=0.104). In the Biogel group,a statistically significant decrease was determined in the VAS values after treatment compared to before treatment (P<0.001). In the placebo group,no statistically significant difference was determined in the VAS values before and after treatment (P=0.157). Conclusion: These types of complementary medicine applications focussed on pain treatment can reduce the disease burden and can probably reduce costs.